2002
DOI: 10.1063/1.1451744
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic interaction among particles in Co–Cr–Ta media and Co/Pt multilayered media evaluated by anomalous Hall effect

Abstract: A new method for evaluating magnetic interaction among the particles in perpendicular magnetic recording layers under canted magnetic field has been proposed using anomalous Hall effect (AHE) measurement and vibrating sample magnetometer (VSM) measurement. Initial curves and magnetic hysteresis loops were measured to determine ΔM, an evaluation index to estimate interaction using the relation as ΔM=Minit−0.5×(Mup+Mdown). The degree of interaction ΔM can be determined as a vector by combining the results obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The corresponding ΔM distribution ( Fig. 2b) is broadened in the sample plane and becomes narrower as the orientation of the field approaches the normal, which demonstrates the independent reorientation of the particle magnetic moments, i.e., the absence of an interaction [11]. The ΔM distribution of a Co/Pt mul tilayered medium has broadening along the normal; at the same time, the form of the ΔM curve does not change with change in the field orientation, which is a consequence of the strong bonding between crystal lites along the normal.…”
Section: Intercrystallite Magnetic Interactions In Magnetic Nanostrucmentioning
confidence: 93%
See 2 more Smart Citations
“…The corresponding ΔM distribution ( Fig. 2b) is broadened in the sample plane and becomes narrower as the orientation of the field approaches the normal, which demonstrates the independent reorientation of the particle magnetic moments, i.e., the absence of an interaction [11]. The ΔM distribution of a Co/Pt mul tilayered medium has broadening along the normal; at the same time, the form of the ΔM curve does not change with change in the field orientation, which is a consequence of the strong bonding between crystal lites along the normal.…”
Section: Intercrystallite Magnetic Interactions In Magnetic Nanostrucmentioning
confidence: 93%
“…It has been demonstrated that an exchange interaction, which is predetermined by the specifics of the formation of starting layers and transits into a mag netostatic interaction when the thickness grows, pre vails in thin Co Cr Pt films. A ΔM distribution that is a vector sum of the ΔM H and ΔM VSM components obtained by means of the anomalous Hall effect with a vibration magnetometer is considered in [11] to characterize the interaction value in Co-Cr-Ta media and Co/Pt multilayered structures for tilted vertical magnetic recording. ΔM H and ΔM VSM are determined from the results of mea surements of the initial magnetization curve (I init ) and also the lower (I down ) and upper (I up ) parts of the hys teresis loop:…”
Section: Intercrystallite Magnetic Interactions In Magnetic Nanostrucmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is difficult to confirm whether they are magnetized together or not, since RE-TM thin films can be perpendicularly magnetized only around the compensation point which has low saturation magnetizaion [3], so that their magnetization is not so sufficient to be detected by a conventional magnetization evaluation method such as VSM. In this study, anomalous Hall effect mesurment was performed to evaluate the magnetization process of soft/RE-TM thin films because its output is inversely proportional to the film thickness hence thin films with low saturation magnetization is thought to be suitable [4,5]. In our previous study, FeCo thin layer behave as a film with perpendicular magnetization up to 2 nm with combination of TbFeCo(50 nm), which is pinned layer for perpendicular MTJ [6].…”
Section: Introductionmentioning
confidence: 98%
“…The segregation, i.e., exchange decoupling, among the ferromagnetic grains, necessary to improve the magnetic behaviour, is obtained mainly with the addition of different elements to ferromagnetic Co, and it is the main aim of the use of alloys for the magnetic layer. The increase of linear density of informations imposes to decrease the layer thickness and the grain size of the magnetic thin film, to reduce demagnetizing field and maintain acceptable signal-noise ratios [1]. It has a negative impact on the thermal stability of the magnetic properties of the films, since it can result in heights of the energy barriers for the magnetization not very far from the thermal energy.…”
mentioning
confidence: 99%